Seasonal variability of water quality for human consumption in the Tilacancha conduction system, Amazonas, Peru - Veneros Guevara, Jaris Emmanuel; Cuchca Ramos, Llandercita; Auquiñivín Silva, Erick Aldo; Oliva Cruza, Manuel; Goñas Goñas, Malluri; García Rosero, Ligia (Technoscience Publications, 2024)
This study evaluated the seasonal variability of water quality in the Tilacancha River, the water source that supplies Chachapoyas, and the rural communities of Levanto and San Isidro del Maino of Perú. Eighteen physical, chemical, and microbiological water parameters were evaluated at five sampling points in two seasons (rainy and dry). To determine water quality, the results obtained for the parameters evaluated were compared with the Maximum Permissible Limits (MPL) established in the Regulation on Water Quality for Human Consumption (DS Nº 031-2010-SA), approved by the Environmental Health Directorate of the Ministry of Health. In addition, a Pearson correlation was performed to estimate the correlation between the variables evaluated. The results showed that microbiological parameters exceeded the MPLs in both periods evaluated, such as the case of total coliforms (44 MPN.100 mL-1), fecal coliforms (25 MPN.100 mL-1), and E. coli (5.45 MPN.100 mL-1), these microbiological parameters reported a positive correlation with turbidity, temperature, total dissolved solids, and flow rate. In addition, aluminum (Al) and manganese (Mn) exceeded the MPL in the rainy (0.26 mg Al.L-1) and dry (1.41 mg.Mn-1.L-1) seasons, respectively. The results indicated that the water of the Tilacancha River is not suitable for human consumption. Therefore, it must be treated in drinking water treatment plants to be used as drinking water.